Pembuatan Prototipe Hunian Sementara untuk Pengungsi di Indonesia - Wilson Edo Santoso; Felecia Felecia; Togar Williater Soaloon Panjaitan (Jurnal Titra, 2016)
Indonesia is a country with highest potential disaster in the world .Some disaster in Indonesia resulted in displaced communities. National Agency for Disaster Management (BNPB) as Indonesian disaster management agency providing emergency shelter for refugees. Problems that arise are refugees have to stay in the emergency shelter for long period of time which should only as an emergency only. This research aims to design a temporary shelter as a bridge between emergency shelters to permanent housing. The design begins with finding the voice of customer (VOC) by way of interviews and news from various media. Results VOC mapped in House of Quality (HOQ) and used as a reference in the design of temporary shelters. Results from this study is the design of temporary shelters and prototype.